Degradation of lateral bearing capacity of piles in soft clay subjected to cyclic lateral loading. Issue 8 (14th September 2019) - Shao, Wei; Yang, Dongyan; Shi, Danda; Liu, Ying
Abstract: In this article, the degradation of the lateral bearing capacity of piles in soft clay subjected to cyclic lateral loading is studied numerically. A modified kinematic hardening constitutive model is employed to simulate the degradation of soft clay after cyclic loading. The modified model is verified by comparing the numerical simulation results with the results of centrifuge model tests. Furthermore, the modified model is applied to numerical simulations for evaluating the lateral bearing capacity of piles in soft clay subjected to cyclic lateral loading. The degradation of the lateral bearing capacity of piles in soft clay after different cyclic displacement levels and different numbers of cycles is investigated. The study reveals that the modified kinematic hardening constitutive model can effectively estimate the cyclic degradation behavior of piles in soft clay subjected to cyclic lateral loading. The degradation of the ultimate lateral bearing capacity progresses slowly with increasing cyclic displacement level for fewer cycles, and the degradation develops significantly at higher levels of cyclic displacement after applying a larger number of cycles.